گیبریل گارشیا مارکیز کے ناول ''تنہائی کے سوسال "کا تجزیہ - Gul Afshan; Dr Tahir Abbas Tayab (Khayaban - خیابان, 2022)
ABSTRACT: Gabriel Garcia Marquez is a famous Latin American novelist, fiction writer, journalist and screenplay writer. He is one of the leading Spanish language authors. His novel "One Hundred Years of Solitude", published in 1967, has become popular all over the world. The first edition in Spanish sold out within a week, and it has been translated in about 30 languages. More than 25 million copies of it were sold out over the next 30 years. The author received the Nobel Prize in Literature in 1982. Marquez is a prominent novelist who, with his creative talents, has skilfully knitted the social and political life of his society and human psychology and conditions in the fabric of events. He has not only delineated many aspects of the daily life of the Colombian natives, including mythological traditions, beliefs, omens and speculations, but has also presented the color of fantasy in the narrative of the story through supernatural elements. His creations have opened many doors of awareness in the world thought and literature. His literary writings are an important milestone.